2020
DOI: 10.15280/jlm.2020.10.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Nutritional and Health Practices Targeting Lifestyle Behavioral Changes in Humans

Abstract: In this 21st century who isn’t enticed by the glamorous and appealing life in the fast lane? We are surrounded by wonders, something we could never have imagined erstwhile. We have everything just a click or a call away. This alluring lifestyle comes with its own perils, the biggest one being concerned with health which is often compromised with check ins and home delivered food but the problem doesn’t just lie with the outside food but also with all those chemical enriched engineered expensive food items. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Furthermore, processed carbohydrates and sweets, may trigger high blood glucose and increase the physiological symptoms of stress, whereas low carb diets may decrease nutrient availability and initiate a cortisol response, resulting in anxiety. Therefore, minimally processed, complex carbohydrates that produce steady streams of glucose may minimize the effect of anxiety and should account for at least 20% of your daily caloric intake [ 12 ], and higher consumption of fibre, fish and Omega-3 fatty acids may be protective to anxiety and anxiety-related disorders [ 13 ]. Nutrients including tryptophan, vitamins B6, B12, A and C, folic acid, tyrosine, phenylalanine, histidine, glutamic acid and choline, are necessary for the production of neurotransmitters, primarily involved in mood, appetite and cognition, such as serotonin, dopamine and norepinephrine [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, processed carbohydrates and sweets, may trigger high blood glucose and increase the physiological symptoms of stress, whereas low carb diets may decrease nutrient availability and initiate a cortisol response, resulting in anxiety. Therefore, minimally processed, complex carbohydrates that produce steady streams of glucose may minimize the effect of anxiety and should account for at least 20% of your daily caloric intake [ 12 ], and higher consumption of fibre, fish and Omega-3 fatty acids may be protective to anxiety and anxiety-related disorders [ 13 ]. Nutrients including tryptophan, vitamins B6, B12, A and C, folic acid, tyrosine, phenylalanine, histidine, glutamic acid and choline, are necessary for the production of neurotransmitters, primarily involved in mood, appetite and cognition, such as serotonin, dopamine and norepinephrine [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Foods contain calories and vital nutrients essential for human growth, development, and survival [ 79 ]. In addition to providing nourishment, food also helped people in many cultures avoid and treat numerous health issues [ 80 ]. The modern era of food science and nutrition reflects the growth of humanity, and advancements have been made thanks to the infusion of knowledge from such fields as medicine, biology, and biochemistry [ 81 ].…”
Section: Effect Of Microgreens On Metabolic Health-promoting Applicat...mentioning
confidence: 99%
“…Nutritional intervention has been evoked as one important tool for protecting the eyes and vision. Natural food and its derivatives play essential roles in health and wellbeing, and it has been characteristically associated with defense mechanisms against microbial agents, xenobiotics and/or physical factors, also demonstrating an immense range of health-promoting perspectives for achieving a pleasant lifespan [33,34]. Large population studies on the role of nutrition in eye health have reported controversial results over decades, mainly regarding cataracts, AMD, RD, OSD/DED, and glaucoma, and also slowing progression of the above sight-threatening diseases, by dietary interventions has also been discussed [6,8,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: State Of the Artmentioning
confidence: 99%